FIRST RECORD OF JUMPING SPIDER Colyttus yiwui (Lin & Li, 2020) (Salticidae) FROM VIETNAM - Thi Thao My, Vi; Ba Hung, Sung; Thi Diep, Phung; Hong Ngoc, Nguyen; Thanh Thuong, Hoang; Long Vuong, Vu; Hoai Thu, Doan; Duc Toan, Vu (HNUE Journal of Science: Journal of Natural Sciences, 2026)
The jumping spider Colyttus yiwui Lin & Li, 2020 (Araneae: Salticidae) is reported for the first time from Vietnam. Specimens, including both males and females, were collected through hand-picking from understorey vegetation in Son La Province, northwestern Vietnam, during fieldwork conducted in 2024 and 2025. The study provides detailed morphological descriptions, measurements, and illustrations of the genital structures for both sexes. The general morphology and genital structures of the specimens are consistent with the original description from Yunnan, China. This record extends the known distribution range of Colyttus yiwui southward from China to Vietnam, contributing new data on the Salticidae fauna of the Indochina region.